Methodology of Lexical Competence Formation of Power-Engineering Students based on CBA and its Experimental Research in Teaching ESP - Botiraliyevna, Bakirova Khilolakhon (Indonesian Journal Publisher, 2024)
This article considers about methodology of lexical competence formation of power - engineering students and its experimental research in ESP teaching. Here some theoretical approaches are discussed, and new methodology suggested by the author is tested in practice. Experimental work was carried out in 3 non-philological universities of the Republic of Uzbekistan as Tashkent State Technical University named after Islam Karimov (TSTU), Fergana Polytechnic Institute (FerPI) and Navoi State Mining Institute (NSMI). Anonymous questionnaires were obtained from students and teachers, written control works are received from students. Using the results obtained, the existing difficulties in teaching and mastering the terms of power engineering were identified. With the help of these difficulties there have been developed a typology of exercises aimed at overcoming the identified challenges. The exercises given here were prepared and published in the textbook